Design Of Antenna For Uhf Rfid Application - Lim, Chin Tiong (Universiti Sains Malaysia, 2017)
For the past decades, the demand for the radio frequency identification (RFID) system has increased and this system offered a better performance in numerous consumer and industrial fields such as the application of automatic identification and object tracking. Recently, the preferred frequency band used in the RFID system is the ultra-high frequency (UHF) band as it has high-speed reading and high data capacity. However, most of the UHF RFID tag antenna are not optimised for its compactness. Based the previous antenna designs, some are found to have flaws due to the weaken fringing field effect and their inability to settle the effect of frequency deviation in Europe UHF RFID system after fabrication. Therefore, this project proposed a modified compact tag antenna design by using folded dipole loop structure with E-segment parasitic element. This proposed tag antenna is used in Malaysia UHF RFID system which is from 919 MHz to 923 MHz and it has dimension of 35 * 35 mm2, using FR-4 as substrate. The frequency deviation caused by the tolerance value in the PCB fabrication is solved by adjusting the parameters of parasitic element. The tag antenna is sent for the PCB fabrication as a prototype to validate the performances and results. The measurement results show the bandwidth has 11 MHz (915.5 - 926.5 MHz) and the return loss